L‐Securinine Induces ROS‐Dependent Apoptosis on Pancreatic Cancer Cells via the PI3K/AKT/mTOR Signaling Pathway - Anastasiou, Ioanna A.; Sarantis, Panagiotis; Rebelos, Eleni; Eleftheriadou, Ioanna; Tentolouris, Konstantinos N.; Katsaouni, Athanasia; Koustas, Evangelos; Kokala, Vasileia; Karamouzis, Michalis V.; Tentolouris, Nikolaos (Wiley, 2025)
Accumulating evidence has shown that l-securinine can, in certain circumstances, suppress tumor development by elevating reactive oxygen species (ROS) levels. The current work set out to examine l-securinine's apoptotic effects on HuP-T3 cells as well as any potential underlying molecular mechanism(s) that could explain its action as an anticancer agent. In this study, we used 1.2B4 cells as a control human cell line to verify our findings. Hup-T3 and 1.2B4 cells were cultured with a medium containing the following dilutions of l-securinine: 1–10 μΜ for up to 72 h. We examined the viability and proliferation levels of cells in both cell lines. Then, we measured only 1.2B4 insulin levels and content. We also quantified cell apoptosis, cell cycle levels, and the intracellular reactive oxygen species on HuP-T3 and 1.2B4. Afterwards, we performed a real-time quantitative polymerase chain reaction and western blot analysis. Our results demonstrated that l-securinine inhibited both proliferation and growth of Hup-T3 cells, showing inhibitory and antiproliferative activity in comparison with the control group. In addition, l-securinine had no impact on the proliferation and growth of 1.2B4 cells, nor on their insulin levels and content. By boosting ROS production, and inhibiting the PI3K/AKT/mTOR signaling pathway, l-securinine induced apoptosis on HuP-T3 cells. Pancreatic cancer was successfully inhibited by l-securinine in vitro. l-securinine triggers ROS-dependent apoptosis on pancreatic cancer cells while inhibiting the PI3K/AKT/mTOR signaling pathway. These findings suggest that l-securinine holds promise as a potential lead for future drug development in the fight against pancreatic adenocarcinoma.